STATISTICAL METHODS IN THE EXPLORATORY STUDY OF DENTINE HARDNESS - Petcu Lucian Cristian; Raftu Gheorghe; Buștiuc Steliana-Gabriela; Briceag Raluca; Caraiane Aureliana (Romanian Society of Oral Rehabilitation, 2021)
The aim of this study was to determine the hardness of dentin using the Vickers hardness test. For dentin were obtained hardness values between 40-78VHN. In the case of dentin, after lifting the load was found a change of indentation geometry, a phenomenon explained by the elastic return of dentin. The return of the material takes place mainly and significantly, in the normal direction of the surface, on which the load is applied. The diagonals of the indentations, remains almost unchanged. The depth of the indentation immediately after penetration and after at an interval of 10 hours showed significant returns, approximately between 20-25%, lower, as the load applied to the hardness test increases, confirming that the dentin has better elastic returns at low loads, and its ability to restructure decreases as local tensions increase.